The meaning of knowledge transfer in educating engineers for modern manufacturing technologies - Piili Heidi; Huusko Anna; Kurvinen Anu; Pikkarainen Ari (United Kingdom, 2025)
The development of modern manufacturing technologies such as additive manufacturing and other laser-based manufacturing technologies have increased their usage, especially in engineering education. Education must correspond to different applications of these technologies to ensure the quality of their usage in the manufacturing industry. Laser-based technologies have an impact on society through companies and industry in the manufacturing sector as they are employing graduated students, who are more aware of the possibilities of the technologies. Traditional manufacturing industries are facing the era of digital transformation. There are vast differences between industries and different industry players as well as their ability to keep up with the transformation process. The pace of the process can depend on many different items that are related to the company organization and leadership, technology base and to the abilities to modify these. The pace can also depend on the processes of cooperation and development between other ecosystem players e.g., supply chain partners or development drivers such as customer industries. This study concentrates on one of the key issues, namely learning and adoption of new skills to tackle the change. Universities have a major role in the knowledge transfer from education to working life. To develop this, there is a need to identify the factors in university training or pedagogical choices that can speed up the process of transformation. The aim of this research is to identify the factors for knowledge transfer through arranging efficient education for laser-based manufacturing technologies, especially in engineering education. It was concluded that by educating engineers with sufficient knowledge about the technologies, the manufacturing industry can utilize the knowledge and implement laser-based technologies better in their operations.
NOLAMP- Nordic Laser Materials Processing Conference (19TH-NOLAMP-2023) 22/08/2023 - 24/08/2023 Turku, Finland